Offsets of Cassini Ovals (Research Journal of Mathematics & Technology, 2022)
We report on computing and visualizing the offsets of the Cassini ovals. We use the eliminationtechnique to obtain offsets as envelopes of a family of planar curves in a recent experimentalversion of GeoGebra. Offset curves are obtained in their implicit form as irreducible polynomialsof degree 12 and 16.